Kesadaran dan Sikap Pengguna Terhadap Privasi Data dalam Penggunaan Aplikasi Sosial Media Tiktok : Studi Kasus Generasi Z - Natasyah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
The development of information technology and the internet has now changed the communication carried out by humans, one of which is through the advancement of social media which has become an integral part of life, it is used to obtain, disseminate and access information. As social media advances, concerns about information security and privacy become increasingly important. Social media has become a common source of leaks of confidential information. Without realizing it, a lot of personal data has been spread on the internet. This leak of personal data can be caused by negligence of the user or service provider. Therefore, information system security is an asset that must be properly protected. Awareness of data privacy and user attitudes towards the use of social media applications have become a major concern in this digital era. This study aims to investigate the level of awareness and attitudes of Generation Z users towards data privacy when using social media applications. Using survey methods and qualitative analysis, this research in-depth investigates the factors that influence users' perceptions of data privacy and attitudes in managing their personal information on social media platforms. It is hoped that the results of this study will provide valuable insights for social media application developers and policy makers to increase awareness and protect user data privacy, especially among Generation Z.